2022
DOI: 10.3390/ijerph19063157
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents and Resilience: Factors Contributing to Health-Related Quality of Life during the COVID-19 Pandemic

Abstract: This study aimed to examine health-related quality of life of adolescents before and during the COVID-19 outbreak, and its relationship to resilience embodied in hope and a sense of coherence. Typically developed adolescents between the ages of 13 to 18 participated in the study; 84 were recruited before the pandemic outbreak and 64 in March to April 2020 during the worldwide outbreak. The participants completed the Pediatric Quality of Life Inventory, Sense of Coherence Scale, and Children’s Hope Scale. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
4
1
Order By: Relevance
“…HRQoL level was higher in our results compared with international population-based studies conducted during the pandemic (mean PedsQL score: 83.8 vs 61.3-79.7) (33)(34)(35). Similarly, in our sample, occurrence of mental health problems was lower than reported in other countries (mean SDQ score: 7.2 vs 10.7-12.1) (35)(36)(37)(38).…”
Section: Association Between Having Been Severely Impacted By the Cov...contrasting
confidence: 63%
“…HRQoL level was higher in our results compared with international population-based studies conducted during the pandemic (mean PedsQL score: 83.8 vs 61.3-79.7) (33)(34)(35). Similarly, in our sample, occurrence of mental health problems was lower than reported in other countries (mean SDQ score: 7.2 vs 10.7-12.1) (35)(36)(37)(38).…”
Section: Association Between Having Been Severely Impacted By the Cov...contrasting
confidence: 63%
“…Hope has also been identified as protective factors against depressive symptoms among college students surrounding COVID-19 outbreak (30). Despite the positive and conducive effect of optimism and hope in maintenance of psychological well-being in people in face of diverse adversities, their correlation with resilience among CS patients was lacking, although existing literature showed that optimistic individuals or those with dispositional hope appear more resilient when addressing negative events, such as oral cancer and COVID-19 outbreak (13,31,32).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our study found that resilience was negatively associated with anxiety symptoms. Adolescents with higher resilience scores experienced lower prevalence of anxiety symptoms, suggesting that promoting resilience can have positive effects on adolescent mental health during the pandemic ( 91 ).…”
Section: Discussionmentioning
confidence: 99%